2014
DOI: 10.3109/09637486.2014.880667
|View full text |Cite
|
Sign up to set email alerts
|

Linkages of biomarkers of zinc with cognitive performance and taste acuity in adolescent girls

Abstract: A cross-sectional study (n = 403) was conducted to examine the relationship of plasma zinc (PZ) and erythrocyte zinc (EZ) levels with cognitive performance and taste acuity for salt in Indian adolescent girls. PZ, EZ and hemoglobin were estimated in schoolgirls (10-16 years). Cognitive performance was assessed by simple-reaction-time (SRT), recognition-reaction-time (RRT), visual-memory, Raven's Progressive Matrices (RPM) test. Taste acuity was determined by recognition-thresholds-for-salt (RTS) using 10 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…At the micronutrient level, two studies found an inverse association between anemia and grade attainment, as well as IDA and cognitive skills such as Raven's Coloured Progressive Matrices among Cambodian male adolescents . Another study provided significant evidence that memory and scores on Raven's progressive matrices test (intelligence) were positively associated with zinc level, while reaction time was negatively associated with zinc levels . Finally, a somewhat older study from Bangladesh associated age at first marriage with weight, showing that greater body weight was associated with earlier age of marriage, even when this effect was adjusted for height, age at menarche, and socioeconomic factors.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…At the micronutrient level, two studies found an inverse association between anemia and grade attainment, as well as IDA and cognitive skills such as Raven's Coloured Progressive Matrices among Cambodian male adolescents . Another study provided significant evidence that memory and scores on Raven's progressive matrices test (intelligence) were positively associated with zinc level, while reaction time was negatively associated with zinc levels . Finally, a somewhat older study from Bangladesh associated age at first marriage with weight, showing that greater body weight was associated with earlier age of marriage, even when this effect was adjusted for height, age at menarche, and socioeconomic factors.…”
Section: Resultsmentioning
confidence: 95%
“…We found only 12 papers that reported on the SCE consequences of adolescent undernutrition . Most of these studies focused on educational outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…A little over a fifth of the female Ghanaian population is adolescent girls (aged 10-19 years) (1) . In addition to physical growth, adolescence is characterised by profound biological, psychosocial and cognitive changes (2,3) related to improved nutrition (4)(5)(6) . Besides the first 1000 d of life, adolescence offers an additional (and last) critical window of opportunity for linear growth catch-up (7,8) .…”
Section: Introductionmentioning
confidence: 99%
“…The design enabled comparative analyses of results from both single vitamin and multivitamin intervention using baseline and follow-up cognitive tests. We measured memory, higher cognitive (executive) functions and mood state, functions previously demonstrated to be negatively affected by micronutrient insufficiency (e.g., Wilkins et al, 2006; Buell et al, 2009; Kesse-Guyot et al, 2011; Chiplonkar and Kawade, 2014).…”
Section: Introductionmentioning
confidence: 99%